1961
DOI: 10.1039/jr9610003138
|View full text |Cite
|
Sign up to set email alerts
|

602. The magnetic properties of some d 3-complexes

Abstract: The magnetic properties of twenty-one complexes of chromium, molybdenum, rhenium, osmium, and iridium have been measured between 80" and 300" K. The results are discussed with reference to the relation between the ligand fields, the interelectronic repulsions, and the spin-orbit coupling of the ions, and to the magnetic exchange between the ions. The results may be accounted for with reasonable values of the parameters after the fourth of these effects has been allowed for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

1967
1967
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 0 publications
4
30
0
Order By: Relevance
“…In addition our magnetic susceptibility data are very similar to those for MiReX, compounds (16,17) where an excellent treatment of the data has been made by Eisenstein (14) using a value of a % 100 x lo-, c.g.s.u. Can.…”
Section: Resultssupporting
confidence: 62%
“…In addition our magnetic susceptibility data are very similar to those for MiReX, compounds (16,17) where an excellent treatment of the data has been made by Eisenstein (14) using a value of a % 100 x lo-, c.g.s.u. Can.…”
Section: Resultssupporting
confidence: 62%
“…Rhenium(IV) is a 5d 3 ion that usually forms inert, relatively stable, octahedral complexes. [8] The high value of the spin-orbit coupling constant of around 1000 cm -1 for the free ion [9] is the main factor responsible for its large magnetic anisotropy. In fact, the combination of spin-orbit coupling and low molecular symmetry explains the SMM behaviour of even mononuclear Re IV compounds, as in the case of the recently reported (NBu 4 ) 2 [ReBr 4 (ox)].…”
Section: Introductionmentioning
confidence: 99%
“…A magnetic moment of 3.23 B.M. at 298 °K was found for CsOsF6 (46), and diffuse reflectance studies of the spectrum have been reported by Brown et al (32) and by Allen et at. (10).…”
Section: C) Hexafluoroosmate(v} Osf6mentioning
confidence: 72%
“…band either the -* t2g or a ~ -* t2g assignment is possible. (31,46). The electronic spectrum in aqueous solution has been studies in some detail by Jorgensen and Schwochau (29), and the principle features of their results are listed in Table 11.…”
Section: Position Assignmentmentioning
confidence: 99%
See 1 more Smart Citation